2011
DOI: 10.3382/ps.2011-01394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipopolysaccharide on the expression of proinflammatory cytokines and chemokines and influx of leukocytes in the hen ovary

Abstract: The aim of this study was to determine whether the expression of proinflammatory cytokines and chemokines in ovarian cells was changed to recruit heterophils and T cells in response to lipopolysaccharide (LPS), a gram-negative bacterial component. White Leghorn laying hens were intravenously injected with LPS or saline and their ovarian follicles and stroma were collected. Changes in the mRNA expression of IL-1β, IL-6, and CXCLi2 in the theca and granulosa layers and ovarian stroma were analyzed by quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
12
0
5
Order By: Relevance
“…Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs. In hens, it has been reported that the oviduct, as well as ovarian follicular and stromal cells, expresses TLRs, AvBDs, as well as proinflammatory cytokines and chemokines, and the expression of these molecules was upregulated by LPS stimulation (Subedi et al 2007, Abdel Mageed et al 2008, Ozoe et al 2009, Woods et al 2009, Abdelsalam et al 2011, Nii et al 2011. Similar to the female reproductive tract, the gene expression data presented in this study revealed that rooster SCs responded to LPS stimulation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs. In hens, it has been reported that the oviduct, as well as ovarian follicular and stromal cells, expresses TLRs, AvBDs, as well as proinflammatory cytokines and chemokines, and the expression of these molecules was upregulated by LPS stimulation (Subedi et al 2007, Abdel Mageed et al 2008, Ozoe et al 2009, Woods et al 2009, Abdelsalam et al 2011, Nii et al 2011. Similar to the female reproductive tract, the gene expression data presented in this study revealed that rooster SCs responded to LPS stimulation.…”
Section: Discussionsupporting
confidence: 66%
“…RT-PCR and quantitative real-time PCR analyses were performed as described previously (Michailidis et al 2010). Quantitative PCR amplification of TLRs, AvBDs, and cytokine genes was performed as described previously (Ebers et al 2009, Michailidis et al 2010, Abdelsalam et al 2011, using the primers listed in Tables 1, 2 and 3. The cycling parameters were as follows: incubation at 95 8C for 3 min, followed by 45 cycles of incubation at 95 8C for 10 s, 56 8C for 8 s for TLRs and cytokines, and 58 8C for 8 s for AvBDs, 72 8C for 8 s, read at 60 8C, followed by a melt curve analysis from 65 to 95 8C with reads at intervals of 0.2 8C and 5 s to confirm amplification of single cDNA products.…”
Section: Rna Isolation Rt-pcr and Quantitative Real-time Pcr Analysesmentioning
confidence: 99%
“…Ovarian follicles infected with gram-negative bacteria cause ovarian disorders and the production of contaminated eggs (Abdelsalam et al, 2011). Escherichia coli is one of the main pathogens causing this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that T cells densities in the vagina are increased by single LPS injection and they returned to the original level within 24 h. However, frequent increase of T cells by repeated LPS injection may be associated with less decrease in T cell density, which eventually formed a pool of T cells in the mucosa. In hen ovary, CD4 + T cells, but not CD8 + T cells, were increased by 6 h after single LPS injection, followed by decreasing tendency by 12 h (Abdelsalam et al, 2011). Consequently, it is suggested that the repeated LPS injection in the vagina may lead the accumulation of T cell subsets in the lamina propria, probably under regulation of chemokines.…”
Section: Of B Cells and Macrophages By Cd4mentioning
confidence: 87%